Where coyotes howl [large type] - Dallas, Sandra (Center Point Large Print, 2023)
"1916. The two-street town of Wallace is not exactly what Ellen Webster had in mind when she accepted a teaching position in Wyoming, but within a year's time she's fallen in love -- both with the High Plains and with a handsome cowboy named Charlie Bacon. Life is not easy in the flat, brown corner of the state where winter blizzards are unforgiving and the summer heat relentless. But Ellen and Charlie face it all together, their relationship growing stronger with each shared success, and each deeply felt tragedy. Ellen finds purpose in her work as a rancher's wife and in her bonds with other women settled on the prairie. Not all of them are so lucky as to have loving husbands, not all came to Wallace willingly, and not all of them can survive the cruel seasons. But they look out for each other, share their secrets, and help one another in times of need. And the needs are great and constant. The only city to speak of, Cheyenne, is miles away, making it akin to the Wild West in rural Wallace. In the end, it is not the trials Ellen and Charlie face together that make them remarkable, but their love for one another that endures through it all."--